Screening Colonoscopy for Colon Cancer in Women during COVID-19 Pandemic - Muhammad Begawan Bestari; Ignatius Ronaldi Joewono (Interna Publishing, 2021)
Colorectal cancer (CRC) is one of the top three leading causes of death in both men and women. However, screening can help detect and prevent CRC. Multiple guidelines recommend CRC screening using stool-based screening and direct visualization via colonoscopy. Anatomically, women have a longer total colonic length, especially in the transverse colon, which makes it redundant; thus it is more difficult to perform complete endoscopy in women. Women also have a higher risk of developing right-sided colon cancer of the flat and depressed type, which is harder to detect than the other types. Moreover, women are less likely to undergo colonoscopy due to embarrassment, especially when the procedure is performed by male gastroenterologists, and the lack of available female gastroenterologists further complicates the problem. The current COVID-19 pandemic also decreases patients' willingness to undergo screening due to the fear of contracting the COVID-19. Delay in diagnosis leads to more advanced tumors upon detection and ultimately decreases the survival rate, especially in women, as they have lower 1-year survival rate when CRC is detected in its later stages than in men. Innovative options for CRC screening have recently emerged, including colon capsule endoscopy, which can be performed in a clinic and may reduce the need for colonoscopy. However, sex-specific CRC screening guidelines and tools are not available. The objective of this review is to identify the barriers and challenges faced when performing screening colonoscopy in women, especially during the pandemic and to encourage the development of sex-specific CRC screening.